Chemical Quality, Preference, and Business Analysis of Kepahiang Robusta Coffee by Roasting Equipment Type - Andwini Prasetya; Methatias Ayu Moulina; Hilda Meisya Arif; Rendi Nofriansyah (SINTA Journal (Science, Technology, and Agricultural), 2022)
The taste of Robusta coffee is largely determined by the way it is processed. The use of roaster and the type of roasting will affect the final result of the roasted coffee. This study aims to determine the panelists' preference for roasted coffee based on organoleptic (color, texture and taste) and to determine the chemical quality (water content and caffeine content) and the feasibility of the best treatment from organoleptic tests. This study used two treatments, namely Roasting equipment and the type of roasting. Roasting equipment consists of semi-automatic and automatic, while the types of roasting consist of light roasted, medium roasted and dark roasted. The results showed that the panelists liked roasted coffee from a roaster using a semi-automatic tool with a medium roasting type. Based on the best treatment, the water content value was 2.68% (meets SNI.01-2983-1992) and caffeine content was 23,177.4 mg/kg with an effort analysis based on the R/C ratio of 1.36 and BEP at 18.735.44 kg.Keywords : roasted coffee, roasting equipment, roasting type, organoleptic, chemical quality